TRICHURIS TRICHIURA INFECTION DIAGNOSED BY HISTOPATHOLOGY: A CASE REPORT - Nizamuddin, Summiya; Latif, Maliha; Ahmad , Asad Hayat (Infectious Diseases Journal of Pakistan, 2023)
We would like to highlight a case of a young female patient who was accidently diagnosed with a Trichuris trichiura infection, when her abdominal resection samples were sent for histopathological studies. The patient was a 16-year-old female patient who presented to her local hospital in Temergara, Lower Dir district with a history of abdominal pain along with abdominal distention for the last 6 months. The patient subsequently underwent a right hemicolectomy procedure and her terminal ileum, cecum, appendix and ascending colon were resected. Suspecting tuberculosis or a malignancy, portions of resections were sent for histopathological studies, to the histopathology section at the Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore. Gross examination of specimen revealed interloop fibrous adhesions between small bowel, large bowel and appendix with some twisting of bowel, but no discrete tumor or polyp was identified. Microscopically, on hematoxylin and eosin stain (H&E) one section of large bowel showed cross-sections of multiple intestinal parasites. To confirm the identification of the parasite, the case was discussed with microbiology and parasitology experts and on closer inspection, the worm was identified as T. trichiura and hence, reported.